Microcystin-LR Degradation and Gene Regulation of Microcystin-Degrading Novosphingobium sp. THN1 at Different Carbon Concentrations - Wang, Juanping; Wang, Chang; Li, Qi; Shen, Mengyuan; Bai, Peng; Li, Jionghui; Lin, Yan; Gan, Nanqin; Li, Tao; Zhao, Jindong (Frontiers in Microbiology, 2019)
The bacterium Novosphingobium sp. THN1 (THN1) is capable of degrading microcystin-LR (MC-LR). To study the ability of THN1 to degrade MC-LR and its possible mechanism(s) of regulation, we analyzed the effect of carbon concentrations on the degradation process. The MC-LR degradation rate peaked early and then declined during MC-LR biodegradation. Decreased levels of carbon in the medium caused the degradation peak to occur earlier. The expression of the functional gene mlrA, encoding a microcystinase, showed a similar trend to the MC-LR degradation rate at various carbon concentrations (r2 = 0.717, p < 0.05), suggesting that regulation of mlrA expression may play an important role in MC-LR degradation by THN1. The total bacterial biomass decreased when the carbon source was limited and did not correlate with the MC-LR degradation rate. Transcriptomic analysis showed that MC-LR degradation differentially regulated 62.16% (2597/4178) of THN1 genes. A considerable number of differentially expressed genes (DEGs) during MC-LR degradation encoded proteins related to carbon-, nitrogen- and amino acid-related pathways. At 2 h of MC-LR degradation, most DEGs (29/33) involved in carbon and nitrogen metabolism were downregulated. This indicated that MC-LR may regulate carbon and nitrogen pathways of Novosphingobium sp. THN1. KEGG pathway analysis indicated that the upregulated DEGs during MC-LR degradation were mainly related to amino acid degradation and substrate metabolism pathways. Particularly, we detected increased expression of glutathione metabolism-related genes from transcriptomic data at 2 h of MC-LR degradation compared with the gene expression of 0 h, such as GST family protein, glutathione peroxidase, S-(hydroxymethyl) glutathione dehydrogenase, and glutathione-dependent disulfide-bond oxidoreductase that have been reported to be involved in microcystin degradation.